2022
DOI: 10.1080/20002297.2022.2161179
|View full text |Cite
|
Sign up to set email alerts
|

Potential oral probiotic Lactobacillus pentosus MJM60383 inhibits Streptococcus mutans biofilm formation by inhibiting sucrose decomposition

Abstract: Streptococcus mutans is known as a contributor to dental caries. In this work, Lactobacillus pentosus MJM60383 was selected for its strong antagonistic activity against S. mutans and was characterized by good oral probiotic properties including lysozyme tolerance, adhesive ability to oral cells, good aggregation (auto-aggregation, co-aggregation) ability, hydrogen peroxide production and inhibition of biofilm formation of S. mutans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Our study first suggested that the growth and biofilm formation by A. actinomycetemcomitans were affected by sucrose. In previous in vitro studies, L. plantarum 9) , L. acidophilus 12) and L. reuteri 25) inhibited the biofilm formation by S. mutans. L. fermentum 26) and L. reuteri 25) reduced the growth of S.…”
Section: Comparison With Previous Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Our study first suggested that the growth and biofilm formation by A. actinomycetemcomitans were affected by sucrose. In previous in vitro studies, L. plantarum 9) , L. acidophilus 12) and L. reuteri 25) inhibited the biofilm formation by S. mutans. L. fermentum 26) and L. reuteri 25) reduced the growth of S.…”
Section: Comparison With Previous Studiesmentioning
confidence: 83%
“…Therefore, it can be suggested that the antibacterial and anti-biofilm activities of L. casei against S. mutans are due to other anti-microbial mechanisms than the acidic environment caused by the production of organic acid and hydrogen peroxide by L. casei. The inhibitory effect of L. casei against S. mutans may be due to the production of bacteriocin or bacteriocin-like polypeptides, which destroy the cell membrane of S. mutans 9,12) and production of biosurfactant 30) , as well as the auto-aggregation and co-aggregation ability to compete with S. mutans for nutrition or adhesive surface 31,32) and the ability of anti-biofilm formation through the inhibition of sucrose decomposition of S. mutans 9) .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mutans causes dental caries and forms biofilms on the tooth surface 17) . L. casei causes advanced dental caries 14) , and colonizes oral tissues to form biofilm 18) . A. actinomycetemcomitans causes aggressive periodontal disease and colonizes dental plaque 19,20) .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…These microorganisms are familiar with and adapted to the human body's environment, so under appropriate usage conditions, probiotic formulations will not cause adverse reactions in the human body (11). Some strains of L. pentosus are derived from naturally fermented foods and possess bioactive effects, making them safe and reliable for potential development as pharmaceutical probiotic formulations (12).…”
mentioning
confidence: 99%